1997
DOI: 10.1097/00000539-199708000-00028
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Nonsteroidal Antiinflammatory Drug (Ketoprofen) on Morphine Respiratory Depression

Abstract: Nonsteroidal antiinflammatory drugs (NSAIDs) decrease the postoperative requirements for opioid analgesic medication. To determine whether NSAIDs potentiate the respiratory effects of opioids, we studied the effects of ketoprofen (K), an NSAID, on respiratory depression induced by morphine (M) in volunteers. After ethics committee approval, 12 healthy male volunteers received infusions of K (1.5 mg/kg), M (0.1 mg/ kg), and KM (1.5 mg/kg + 0.1 mg/kg) in a double-blind, randomized, three-treatment, three-period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…This general principle has already been established in postoperative pain, where combined administration of NSAID enhance the analgesic efficacy of opioids 1,2 but, if anything, reduce the severity of respiratory depression. 31 The findings also suggest new avenues for development of medications involving combinations of lowered doses of opioids and specific 5-LOX inhibitors. Such combinations have the potential to reduce the side effects commonly experienced when using powerful opioid analgesics, such as morphine.…”
Section: Discussionmentioning
confidence: 93%
“…This general principle has already been established in postoperative pain, where combined administration of NSAID enhance the analgesic efficacy of opioids 1,2 but, if anything, reduce the severity of respiratory depression. 31 The findings also suggest new avenues for development of medications involving combinations of lowered doses of opioids and specific 5-LOX inhibitors. Such combinations have the potential to reduce the side effects commonly experienced when using powerful opioid analgesics, such as morphine.…”
Section: Discussionmentioning
confidence: 93%
“…Local anaesthetic agents combined with opioids intrathecally may act synergistically and produce good surgical anaesthesia and excellent postoperative analgesia, thus reducing the total dose of each drug [20][21][22][23]. Similarly, the different sites of analgesic action found with NSAIDs and opioids also suggest additive, or possibly even synergistic effects, and in clinical practice they are often used in combination [24,25]. The opioid-sparing effect of NSAIDs may lead to a reduction in opioid-induced side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…Another survey was carried out in 29 provinces/ municipalities of China, with 933 Chinese health professionals, of whom 819 were physicians. The survey showed that they rated the top two barriers to optimal cancer management as a fear of opioid addiction and the overly restrictive regulations about opioids (Moren et al, 1997).…”
Section: Physicians' Concern About Using Opioids For Cancer Painmentioning
confidence: 99%